PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN PROMOSI TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA PRODUK INDOMIE DI SUPERINDO KECAMATAN BABELAN, KABUPATEN BEKASI - John EHJ FoEh; Dimas Priyo Anggoro (Ultima Management : Jurnal Ilmu Manajemen, 2022)
Abstract- The purpose of this study was to determine the effect of the independent variables, namely brand image, product quality and promotion on the dependent variable, namely consumer loyalty through the intervening variable, namely customer satisfaction. This research was conducted in Superindo, Babelan District, Bekasi Regency. The method used in this study is a quantitative method. The data used in this study is primary data using a questionnaire. The sampling method in this study used the Accidental Sampling technique. The population of this research is all consumers who visit Superindo, Babelan District, Bekasi Indomie Regency, which an average of 580 visitors in a month. The number of samples used in this study was 221 respondents calculated using the table for determining the number of samples developed by Isaac and Michael. The method of analysis uses Descriptive Quantitative Analysis, Multiple Linear Regression Analysis and Path Analysis. The data was processed using SPSS version 25 data analysis software. The results of this study indicate that brand image, product quality and promotion simultaneously or partially have a positive and significant effect on consumer satisfaction, while brand image, product quality and customer satisfaction partially have a positive and significant effect on consumer loyalty of Indomie products in Superindo, Babelan District, Bekasi Regency Keywords: Consumer Loyalty; Brand Image; Product Quality; Promotion; Consumer Satisfaction